2020
DOI: 10.1111/acps.13264
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma clozapine concentration and clinical outcome: a cross‐sectional study

Abstract: There is no report that statistically evaluates the therapeutic reference (350-600 ng/ml) and adverse drug reaction (ADR) range (>1000 ng/ml) of clozapine (CLZ) recommended by the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie (AGNP) consensus guidelines in an isolated and large sampling study. Methods: We administered CLZ to 131 Japanese patients with treatment-resistant schizophrenia in a multicenter cross-sectional study. Plasma CLZ concentrations were assayed by high-performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Eight high‐quality studies with 358 participants had data on clozapine dose as well as C/D ratio, with no difference between lower or higher clozapine dose or C/D ratio and response 17,18,20,23,24,26,30,35 . ( and ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight high‐quality studies with 358 participants had data on clozapine dose as well as C/D ratio, with no difference between lower or higher clozapine dose or C/D ratio and response 17,18,20,23,24,26,30,35 . ( and ).…”
Section: Resultsmentioning
confidence: 99%
“…It appears that a proportion of patients require a minimum level around 350 ng/ml, while others would require concentrations of around 650 ng/ml to achieve significant symptom reduction. A similar study 12 found higher clozapine plasma concentrations (above 1000 ng/ml) to be associated with better clinical response, however more adverse effects. The exact pharmacological mechanism by which clozapine exerts its clinical efficacy is still unknown.…”
Section: Discussionmentioning
confidence: 64%
“… 9 Yet substantial conflicting data exist regarding any relationship between clozapine plasma concentrations and therapeutic response. 10 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the total cumulative dose of clozapine achieved after six months of treatment was significantly describing the exposure to the drug, taking into account both the dose and time. Recently, higher clozapine doses, concentrations, and treatment durations were reported in responders as compared to non-responders [ 32 ]. Furthermore, waiting for a delayed clozapine response for persistent positive symptoms was recommended over plasma level-guided dose escalation in the recent consensus recommendations by the TRRIP working group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%